2022
DOI: 10.4236/aad.2022.114004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy of Photobiomodulation for Moderate and Advanced Dementia or Alzheimer’s Disease: Case Studies

Abstract: Extensive research is ongoing in the use of Photobiomodulation (PBM, often referred to as low-level or cold laser therapy) to treat Alzheimer's disease as well as other debilitating diseases. The following case studies further confirm that PBM could be a breakthrough approach to limit the progression of insidious diseases. We present four cases, two with mild to moderate dementia and two with more advanced symptoms. Several publications have shown beneficial results, however, several weeks of daily treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The clinical studies of the PBM effects for AD are still limited [ 9 , 10 , 11 , 19 , 85 ]. Table 2 summarizes the results of recent clinical studies on the therapeutic effects of PBM in patients with AD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical studies of the PBM effects for AD are still limited [ 9 , 10 , 11 , 19 , 85 ]. Table 2 summarizes the results of recent clinical studies on the therapeutic effects of PBM in patients with AD.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, in experimental and clinical studies, PBM is performed in awake subjects [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. In our recent review, we suggested that there are no commercial devices for simultaneous PBM and sleep monitoring, which significantly limits the clinical investigations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the development of effective methods for stimulation of MLV functions is highly relevant for medicine. Recently, non-invasive transcranial photobiomodulation (PBM) has been proposed as a novel alternative method for therapy for dementia and AD as well as a promising approach in the improvement of cognitive functions in healthy subjects [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]. It is believed that the therapeutic effects of PBM are based on reducing neuroinflammation and activation of anti-oxidant systems through the improvement of metabolism and microcirculation of the brain, leading to neuroprotection [ 133 , 138 , 139 , 141 ].…”
Section: Meningeal Lymphatics As a Target For Anti-amyloid Therapymentioning
confidence: 99%